The effect of atmospheric pressure on oxygen saturation and dyspnea: the Tromsø study - Dohmen, Lisa M. E.; Spigt, Mark; Melbye, Hasse (International Journal of Biometeorology, 2020)
A drop in atmospheric pressure, as observed at high altitudes, leads to decreased oxygen saturation. The effect of regular changes in barometric pressure at sea level has never been studied in a general population. A cohort of adults aged 40 years were examined with pulse oximetry at two separate visits, and the local barometric pressure was available from the local weather station. The study aimed at determining the effect of atmospheric pressure on oxygen saturation also called SpO 2 , as well as on shortness of breath. Based on spirometry, the participants were divided into two groups, with normal and decreased lung function. Decreased lung function was defined as forced expiratory volume in 1 s (FEV 1 ) below lower limit or normal (LLN) or FEV1/FVC (FVC, forced vital capacity) below LLN, with GLI 2012 reference values. The statistical analysis included uni/multivariable linear and logistic regression. A total of 7439 participants of the Tromsø 7 cohort study were included. There was a significant association between barometric pressure and SpO 2 < 96%, and we found that a reduction of 166.67 hPa was needed to get a 1% reduction in SpO 2 . The change in atmospheric pressure was not significantly associated with shortness of breath, also not in subjects with reduced lung function.